SELEÇÃO E CARACTERIZAÇÃO MOLECULAR DE BACILLUS THURINGIENSIS BERLINER COM ATIVIDADE TÓXICA PARA TRICHOPLUSIA NI HUEBNER (LEPIDOPTERA: NOCTUIDAE) - Grecco, E.d. (2021)
Trichoplusia ni is a polyphagous pest that is becoming a major pest in plantations of cruciferous crops, soybeans and cotton. This study was aimed to select and molecularly characterize efficient isolates of Bacillus thuringiensis (Bt) for the control of T. ni. For the bioassays of pathogenicity, an aliquot with a 3 x 108 spores/mL suspension of Bt of each isolate was applied on the surface of the artificial diet disk, previously distributed on acrylic plates with 50 larvae, distributed in 5 repetitions. In bioassays to obtain the LC50, only isolates with 100% mortality were preselected, and tests were carried out at the concentrations 102, 5 x 102, 103, 2 x 103, 4 x 103, 6 x 103, and 8 x 103 spores/mL, and the treatments consisting of 120 larvae, distributed in 3 repetitions. A molecular characterization was performed to detect the genes cry1, cry2 and Vip for the isolates which obtained mortality over 95%. Isolates HD-1 (Standard), Bt-1043N-V, Bt-1034F, Bt-1009K, Bt-1000 and Bt-969A caused 100% mortality in the test for pathogenicity and presented an LC50 of 1.17 x 103, 1.45 x 103, 1, 46 x 103, 1.01 x 103, 9.43 x 102, 1.22 x 103, respectively. Genes cry1, cry2 and Vip were not found in the isolates tested, and other Cry toxins may have been causing the mortality of T. ni, since the isolates tested are specific for the Lepidoptera order. These isolates showed potential for the control of T. ni, being aggressive to this insect, with a potential to be used in a pest management program for this species.